Effectivity System of Management Information in Information Tehcnology Center University of Sam Ratulangi Manado. - Kalalo, Intani Kirana; Mandey, Jantje; Pombengi, Jericho (Sam Ratulangi University, 2015)
ABSTRACT In accordance with Regulation of the Minister of Education and Culture of the Republic of Indonesia on the Organization and Work of Sam Ratulangi University of article 105, paragraph 1, which states that the Information and Communication Technology Unit is a unit of the technical implementation in the field of development and management of systems and information and communication technology. And Article 106, namely, Information and Communication Technology Unit has the tasks of system development and management of information and communication technology as well as the provision of information and communication technology services. This study used a qualitative method, data source or informant study of 10 people in the capture of some elements, such as students 8 people, and Lecturer 2 people. Collecting data using questionnaires, interviews, and documentation. Based on the research, it can be concluded that the effectiveness of management information systems at the center of the information technology (PTI) Sam Ratulangi University, yet effective. Timeliness, accuracy of information, and human resources must be developed. As well as the facilities and infrastructure must also be added. Keywords: effectiveness, management information system